(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to examine the level of inclusion of sustainable development dimensions in the sixth-grade science textbook in light of Saudi Vision 2030, focusing on the social, environmental, and economic dimensions. The descriptive analytical method using content analysis was employed. The content of the sixth-grade science textbook for both the first and second semesters of the academic year (1447–1448 AH) was analyzed. The research instrument consisted of a content analysis checklist including 67 indicators distributed across the three dimensions of sustainable development. The results showed varying levels of inclusion of sustainable development dimensions. The social dimension ranked first, accounting for (57%) in the first semester and (27%) in the second semester. It was followed by the environmental dimension with (11%) in the first semester and (1%) in the second semester, while the economic dimension ranked last with (8%) in the first semester and (4%) in the second semester. These findings indicate a clear imbalance in the distribution of the three dimensions, with a stronger emphasis on social aspects related to thinking and learning skills, while several environmental and economic indicators were weakly represented. The study recommends strengthening the integration of sustainable development dimensions in science curricula and achieving a better balance among them to enhance students’ awareness of sustainability issues and support the goals of sustainable development and Saudi Vision 2030.